Cyclodextrin-Appended Superparamagnetic Iron Oxide Nanoparticles as Cholesterol-Mopping Agents - Antonino Puglisi; Simone Bassini; Simone Bassini; Erik Reimhult (Frontiers in Chemistry, 2021)
Cholesterol plays a crucial role in major cardiovascular and neurodegenerative diseases, including Alzheimer’s disease and rare genetic disorders showing altered cholesterol metabolism. Cyclodextrins (CDs) have shown promising therapeutic efficacy based on their capacity to sequester and mobilise cholesterol. However, the administration of monomeric CDs suffers from several drawbacks due to their lack of specificity and poor pharmacokinetics. We present core-shell superparamagnetic iron oxide nanoparticles (SPIONs) functionalised with CDs appended to poly (2-methyl-2-oxazoline) polymers grafted in a dense brush to the iron oxide core. The CD-decorated nanoparticles (CySPIONs) are designed so that the macrocycle is specifically cleaved off the nanoparticle’s shell at a slightly acidic pH. In the intended use, free monomeric CDs will then mobilise cholesterol out of the lysosome to the cytosol and beyond through the formation of an inclusion complex. Hence, its suitability as a therapeutic platform to remove cholesterol in the lysosomal compartment. Synthesis and full characterization of the polymer as well as of the core-shell SPION are presented. Cholesterol-binding activity is shown through an enzymatic assay.